2019
DOI: 10.1017/s0007114519003179
|View full text |Cite
|
Sign up to set email alerts
|

Association of dietary acid load and plant-based diet index with sleep, stress, anxiety and depression in diabetic women

Abstract: Diabetes is a common chronic disease with various complications. The present study was conducted to determine the association of plant-based diet index (PDI) and dietary acid load (DAL) with sleep status as well as mental health in type 2 diabetic women. In this cross-sectional study, a validated FFQ was used to assess dietary intakes of 230 diabetic patients. We created a whole PDI, healthful PDI (hPDI) and unhealthful PDI (uPDI). DAL was calculated based on potential renal acid load and net endogenous acid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 55 publications
6
49
0
1
Order By: Relevance
“…Their study concluded an improvement in these markers and proposed novel microbiome-related pathways through which plant-based diets can modulate the microbiome [ 33 ]. A recent study published in 2019 by Daneshzad et al , sought to compare plant-based dietary index and dietary acid load with sleep status as well as mental health in Type 2 diabetic women [ 34 ]. The study concluded that participants with higher dietary acid load scores and patients who adhered to animal-based rather than plant-based diets were more likely to be poor sleepers and have mental health disorders.…”
Section: Nutrition and Its Impact On The Microbiome And Mental Statementioning
confidence: 99%
“…Their study concluded an improvement in these markers and proposed novel microbiome-related pathways through which plant-based diets can modulate the microbiome [ 33 ]. A recent study published in 2019 by Daneshzad et al , sought to compare plant-based dietary index and dietary acid load with sleep status as well as mental health in Type 2 diabetic women [ 34 ]. The study concluded that participants with higher dietary acid load scores and patients who adhered to animal-based rather than plant-based diets were more likely to be poor sleepers and have mental health disorders.…”
Section: Nutrition and Its Impact On The Microbiome And Mental Statementioning
confidence: 99%
“…Other studies also have shown that a higher diet quality is linked to a reduced risk of sleep disorders (23,24). Overall, it seems that consumption of high-quality diets, rich in fruits and vegetables, is linked to a reduced risk of SDs, while, adherence to a dietary patterns with high amounts of saturated fatty acids and animal food items and low amounts of fruit and vegetables is linked to an elevated risk of SDs (25)(26)(27).…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that PRAL has better predictive values than NEAP when minerals other than potassium play important roles in disease development. For instance, PRAL is more predictive of cardiovascular mortality among patients who underwent coronary artery bypass grafting surgery [11] and of depression [45,46]. Other minerals, such as magnesium and calcium, do play important roles in heart functions [47,48] and in the development of depression [49][50][51].…”
Section: Discussionmentioning
confidence: 99%